Physical modeling low-waste technological process of the round forging hot stamp - Telegin Igor (EDP Sciences, 2021)
The paper presents the results of an experimental study highly efficient technological process manufacture of the round forging on a crank hot-stamping press. The high efficiency of this technological process is achieved by reducing its metal consumption. To this end, at the final stamping transition, the forging forging radii were reduced and, accordingly, the allowances for subsequent machining were minimized.